ACCOUNTING REQUIREMENTS OF STOCK EXCHANGES, 1933. - Smith, Frank P. (The Accounting Review, 1937)
Abstract The article presents a study that is an attempt to describe and evaluate requirements of some leading securities exchanges as of 1933. The need of stockholders for corporate reports has tended to coincide with the increasing importance of corporations as a type of business organization. But many factors other than wishes of stockholders have influenced the development of corporate reporting and accounting policies. In the early period of corporate regulation in the U.S., the legislation restricting operations of railroads possibly exerted some influence; some of the leading financial journals carried on active campaigns for better reporting practices. Stock exchanges, the factor with which the paper is principally interested, began to require accounting statements as a part of their expanding listing requirements. Prior to 1938, legislation played, but a minor part in the development of reporting and accounting policies of American industrial corporations. These legislative devices represent new approaches to the problem of securing adequate presentation of corporate operations.